Posted by steve on Saturday, March 8, 2008 at 5:49pm.
Add the first and the second ---> 2x = 39
x = 19
add the first and the third ----> 2x + 3z = 47
38 + 3z = 47
z = 3
now put those values back into the second
19 - y - 3 = 8
y = 8
i am 50 years old, i am sorry but i need this spelled out for me if possible
Well Steve, I am 68 years old, lol
I assume you are solving these equations?
x + y + z = 30 ---- first equation
x - y - z = 8 -----second equation
2x + 0 + 0 = 38 ---- I added them
x = 19 divided by 2, we now know x
x + y + z = 30 --- first equation again
x - y + 2z = 17 --third equation
2x + 0 + 3z = 47 ---- added them
2x + 3z = 47 , but we know x = 19 so..
38 + 3z = 47
3z = 47 - 38
3z = 9
z = 3 , so now we have x=19 and z=3
let's put this back into the first, or any one really
x + y + z = 30
19 + y + 3 = 30
y + 22 = 30
y = 30-22
y = 8
so x=19, y=8, and z=3
notice those values work in all 3 equations.
Reiny,thanks so much for your help on this!!!!!!!!!!!